Internet of things and industry 4.0: systematic bibliometric review - Pedro Mendes Albuquerque, João; Renato Soares Lima, Paulo; Beatriz Marcelino Rodrigues, Ana; Leão Lima, Davi; Bessa Porto Pinheiro Vasques, Karine (Seven Editora, 2023)
With the development and proliferation of technological standards of the Fourth Industrial Revolution in Brazil, it becomes necessary to know new methods that help in industrial processes. In this venom, this article aims to analyze and expose studies related to the aplication of the main concepts of IoT (Internet of Things) in industrial processes and business complexes. A search was carried out, with a time frame from 2014 to 2022, in bibliographic collections for theoretical references and research already carried out on the subject. The result, observed in the research conducted, identified that, although they bring greater aid to companies that adopt this technology, there are economic and technological aspects, which should be considered in relation to the implementation of IoT in the industrial and business sectors. It is concluded that The IoT presents gains for companies (such as higher productivity and productive efficiency) and their final consumers (such as quality control, lower value and safety), although it still faces challenges for implementation in several areas. DOI: https://doi.org/10.56238/tfisdwv1-067